Science and Religion in the Context of Modern Society - Reddy, Dr. V. Bhargavi; Rajani, Dr. N. Sree; Santhi, Dr. M. (The journal of contemporary issues in business and government, 2022)
The 1921 Physics Nobel Prize Winner, Albert Einstein in his 1941 “Science and Religion” expressed that “Science without religion is lame, religion without science is blind”. His deep conviction and concern for “religion and God” also have been expressed in his obituary issue of New York Times of April 15, 1955 thus: “My religion consists of a humble admiration of the illimitable superior spirit Who reveals Himself in the slight details we are able to perceive with our frail and feeble minds. That deeply emotional conviction of the presence of Superior Reasoning Power, which is revealed in the Incomprehensible Universe, forms my idea of God.”